Distance Learning in Algeria and the Challenge of the Digital Divide (El-Wahat Journal for Research and Studies, 2026)
The digital divide poses a major challenge that affects Distance Learning in the age of digital transformation. The quality of education is directly influenced by the disparity in the availability and use of digital technologies. This study seeks to investigate the concept and dimensions of the digital divide and to evaluate its implications for higher education through a set of indicators. It also discusses the reality of distance learning in Algeria, highlighting the specific challenges it faces, particularly those related to weak digital infrastructure, lack of training, and differences in digital skills. The study concludes with a set of recommendations aimed at reducing the digital divide and strengthening digital capacities to enhance the quality of higher education